Amber workshops in central Poland during the Roman Period (AmS-Skrifter, 2026)
Archaeological research conducted since the 1960s in the western Mazovia (central region of Poland), has unveiled an extensive iron production centre from the late pre-Roman and Roman periods, referred to as the Mazovian Centre of Metallurgy. This centre, established by the people of the Przeworsk culture, who inhabited vast areas of southern and central Poland from the 2nd century BC to the midd 5th century AD, indicates a significant scale of local iron production, constituting a crucial aspect of the regional economy. However, iron production was not the only branch of the local economy. Relics of amber workshops have been recorded on several settlements. Within them, remains of all stages of amber processing have been discovered: lumps of raw material, semi-finished and finished products (mainly beads). The presence of amber workshops in the western Mazovia is somewhat surprising, as amber does not occur naturally in this part of Poland. Its influx could have been linked to a long-distance exchange, including iron produced in the region.